Powtoon-Assisted Audio-Lingual Method: An Effective Strategy for Enhancing Students’ Vocabulary Mastery in Al-Sajadah Islamic Integrated Secondary School Riau - Nur Akila; Kasmiati Kasmiati; Maulana Malik Fauzi; Arif Fedianto; Muhammad Hattamy; Rahmat Aminullah (Prodi Pendidikan Keagamaan Islam, 2026)
This research aimed at finding out the effectiveness of Sam’iyyah Syafawiyah method with Powtoon media in increasing student vocabulary mastery at the eighth grade of Islamic Integrated Junior High School of As-Sajadah Pekanbaru. It was quantitative experiment research with quasi-experimental design in the form of nonequivalent control group design. All the eighth-grade students at Islamic Integrated Junior High School of As-Sajadah Pekanbaru in the Academic Year of 2024 were the population of this research, and they were 91 students. The samples selected by using purposive sampling technique were 44 the eighth-grade students—22 students of class 4 as the experimental group and 22 students of class 3 as the control group. Observation, test, and documentation were the techniques of collecting data. The techniques of analyzing data were validity test, reliability test, normality test, homogeneity test, and t-test. The research findings indicated that Sam’iyyah Syafawiyah method with Powtoon media was effective in increasing student vocabulary mastery at the eighth grade of Islamic Integrated Junior High School of As-Sajadah Pekanbaru. It was proven with the score of t-test statistic test, the score of tobserved 11.573 was higher than ttable 2.086, and the significance level 0.000 was lower than 0.05. So, Ha was accepted, and H0 was rejected.